The development of visual categorization based on high-level cues - Peykarjou, Stefanie; Höhl, Stefanie; Pauen, Sabina (Child development, 2024)
This study investigated the development of rapid visual object categorization. N = 20 adults (Experiment 1), N = 21 five to six-year-old children (Experiment 2), and N = 140 four-, seven-, and eleven-month-old infants (Experiment 3; all predominantly White, 81 females, data collected in 2013-2020) participated in a fast periodic visual stimulation electroencephalographic task. Similar categorization of animal and furniture stimuli emerged in children and adults, with responses much reduced by phase-scrambling (R2 = .34-.73). Categorization was observed from 4 months, but only at 11 months, high-level cues enhanced performance (R2 = .11). Thus, first signs of rapid categorization were evident from 4 months, but similar categorization patterns as in adults were recorded only from 11 months on.
Gesehen am 15.12.2023